Сільськогосподарська термінологія в україномовнихта англомовних словниках - Тішечкіна, К.В. (Мовознавство, 2013)
Стаття присвячена дослідженню сільськогосподарської термінології. Розглянуто поняття «термін» та проаналізовано лексико-семантичні особливості деяких термінів аграрної галузі (газон, ґрунт, ділянка, долина та ін.) за допомогою словників української та англійської мов. Ukraine is a valuable agricultural country for international community, so further development of our country will be associated with this area. Foreign investments and partnerships require detailed translation of documents and various recommendations on the use of land resources of our country. Therefore, accuracy of translation of agricultural terminology is the key to proper and effective use of Ukrainian lands. The article deals with some agriculture terminology. The concept «term» is described and lexical-semantic features of certain terms of the agricultural sector (such as lawn, soil, plot, valley etc.) are analyzed using Ukrainian and English dictionaries. Data from 7 dictionaries of Ukrainian, English and Russian languages had been provided as the sources of the research. The entire row of researched terms retains lexical meaning both in Ukrainian and in English lexicographical sources (soil scientist, soil science, soil-cultivating, soil fatigue, soil formation, valley). Among the considered words not all of them have a clear translation (газон, ґрунт, ґрунтовий, ділянка). Many words are inherent with synonyms during translation. Ukrainian versions of the terms «ґрунтообробний», «ґрунтостомлення», «ґрунтоутворення» are one-component, English versions are multi-component. The terms «ґрунтознавець», «ґрунтознавство» in English, are presented in two versions, one of which is a single-component and the other is a two-component. The paper presents some recommendations for the use of an alternative translation of agricultural terms. The results of research can be used to writing books related to agricultural sector, and translation of various agricultural documents and recommendations.